PENGEMBANGAN SISTEM INFORMASI KEUANGAN PADA BSKM KELURAHAN LABUH BARU TIMUR DI KOTA PEKANBARU - Fadhilla, Mutia; Abdillah, Muhammad Rasyid; Anita, Rizqa (Komunitas Manajemen Kompetitif, 2023)
BSKM is a social institution in the community which was formed with the aim of providing death care services to the Muslim community. Currently, the membership and financial data management system at BSKM is still running using a manual and non-computerized system. This community service is carried out to resolve these problems. Specifically, this community service is conducting web-based information system development that help the partner institution at managing financial data. Based on the results, the process of managing membership and financial data at the partner institution becomes more effective and efficient compared to the current process. Apart from that, institutional administrators also are greatly helped by this financial information system that has been developed.